2023
DOI: 10.1002/brb3.2860
|View full text |Cite
|
Sign up to set email alerts
|

Effect of add‐on melatonin on seizure outcomes and quality of sleep in epilepsy with idiopathic generalized tonic‐clonic seizures alone in adult patients: Cross‐sectional, randomized, double‐blind, placebo‐controlled clinical trial

Abstract: Background Effective treatment of epilepsy is a major challenge in the field of neurology. Studies have suggested that melatonin can work in epilepsy with a good safety profile. Objectives This study was performed to determine the effectiveness of melatonin in seizure outcomes, as well as the quality of sleep in patients with generalized epilepsy. Methods In this cross‐over clinical trial study, 60 patients with epilepsy with idiopathic generalized tonic‐clonic seizures alone (EGTCS) and under valproic acid tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…29 Moreover, treatment of epileptic rodents and patients with melatonin has shown anticonvulsive effects. [30][31][32] This seems, however, to be dependent on melatonin concentrations, with too high melatonin concentrations also having proconvulsive effects. 33 In patients, despite showing normal rhythmicity, melatonin levels have been reported to be lower when compared to control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Moreover, treatment of epileptic rodents and patients with melatonin has shown anticonvulsive effects. [30][31][32] This seems, however, to be dependent on melatonin concentrations, with too high melatonin concentrations also having proconvulsive effects. 33 In patients, despite showing normal rhythmicity, melatonin levels have been reported to be lower when compared to control.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is the primary hormone integrating sleep–wake cycle and circadian rhythms 29 . Moreover, treatment of epileptic rodents and patients with melatonin has shown anticonvulsive effects 30–32 . This seems, however, to be dependent on melatonin concentrations, with too high melatonin concentrations also having proconvulsive effects 33 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, melatonin showed beneficial effects in animal models of iron‐induced, 114 penicillin‐induced, 115 pentylenetetrazol‐induced, 116 and kainate‐induced seizures 117 . Recent clinical trials support the use of melatonin as an add‐on to improve seizure frequency or severity 118,119 . However, earlier studies have been deemed of poor methodological quality and did not allow for a univocal conclusion on the subject 120 .…”
Section: Discussionmentioning
confidence: 99%
“…117 Recent clinical trials support the use of melatonin as an add-on to improve seizure frequency or severity. 118,119 However, earlier studies have been deemed of poor methodological quality and did not allow for a univocal conclusion on the subject. 120 The findings presented here indicate that the possible benefits of the use of melatonin in epilepsy are worth further research.…”
Section: Kir21 Protein Trafficking To the Plasma Membrane Was Not Alt...mentioning
confidence: 99%
“…Another study found a decrease in seizures in children who took exogenous melatonin to improve sleep [ 46 ]. In patients with epilepsy with idiopathic generalized tonic-clonic seizures, Maghbooli et al found that the addition of melatonin to patients’ valproic acid treatment was associated with a significant reduction in the severity of epilepsy and improvement in sleep quality [ 47 ].…”
Section: Melatonin: Usage and Considerationsmentioning
confidence: 99%